Beyond Words: Teaching English and Promoting Religious Moderation through the Reconstruction of Reading Texts - Lina, Marisa Fran; Rokhmiyati, Sri; Suriyah, Eni (Institut Agama Islam Negeri Kudus, 2025)
The character value of tolerance among students has been eroded by the challenges of this disruptive era, necessitating efforts to reinforce it through religious moderation. Meanwhile, English texts can be a solution to instilling religious moderation on a larger scale. Besides, it enriches students’ English skills. However, English reading text with Islamic value is limited and difficult to find. As a result, this study aims to remake texts using religious moderation for English learning and reveal the role of technology in remaking religious moderation reading texts. The qualitative descriptive method is used, and the data collection techniques were interview, observation, and documentation. The finding shows a five-phase framework for developing religious moderation-oriented reading texts: (1) selecting and adapting English texts from verified online sources, (2) conducting a needs analysis aligned with foundational and core competencies in reading skills, (3) contextualizing religious moderation principles into the texts, (4) embedding moderation values through deliberate modifications to narrative elements (e.g., characterization, settings, and plotlines), and (5) designing evaluative quizzes to assess both comprehension of moderation values and English proficiency. This systematic approach ensures the dual pedagogical objectives of fostering religious moderation awareness and enhancing literacy skills are met through culturally responsive material design. In addition, the technology helps the teacher in recreating the English text activity, specifically in searching for relevant and credible reading text resources. It also enhances teachers' creativity to present a more interesting text and quiz.